Occlusal load modelling significantly impacts the predicted tooth stress response during biting: a simulation study. Issue 7 (18th May 2020) - Saini, Harnoor; Ackland, David C.; Gong, Lulu; , Leo K.; Cheng,; Röhrle, Oliver
Abstract: Computational models of the masticatory system can provide estimates of occlusal loading during (static) biting or (dynamic) chewing and therefore can be used to evaluate and optimize functional performance of prosthodontic devices and guide dental surgery planning. The modelling assumptions, however, need to be chosen carefully in order to obtain meaningful predictions. The objectives of this study were two-fold: (i) develop a computational model to calculate the stress response of the first molar during biting of a rubber sample and (ii) evaluate the influence of different occlusal load models on the stress response of dental structures. A three-dimensional finite element model was developed comprising the mandible, first molar, associated dental structures, and the articular fossa and discs. Simulations of a maximum force bite on a rubber sample were performed by applying muscle forces as boundary conditions on the mandible and computing the contact between the rubber and molars (GS case). The molar occlusal force was then modelled as a single point force (CF1 case), four point forces (CF2 case), and as a sphere compressing against the occlusal surface (SL case). The peak enamel stress for the GS case was 110 MPa and 677 MPa, 270 MPa and 305 MPa for the CF1, CF2 and SL cases, respectively. Peak dentin stress for the GS case was 44 MPa and 46 MPa, 50 MPa and 63 MPa for the CF1, CF2 and SL cases, respectively. Furthermore, the enamel stress distribution was also strongly correlated to the occlusal load model. The way in which occlusal load is modelled has a substantial influence on the stress response of enamel during biting, but has relatively little impact on the behavior of dentin. The use of point forces or sphere contact to model occlusal loading during mastication overestimates enamel stress magnitude and also influences enamel stress distribution.